Combining Docking And Molecular Dynamic Of Protease From Bacillus Lehensis G1 - Noorul Aini Sulaiman; Shuhaila Mat-Sharani; Nor Muhammad Mahadi; Nur Zazarina Ramly (RMP Publications, 2024)
Volume 2, Issue 1